Two new dwarf species of Homalolepis (Simaroubaceae) from the Brazilian Cerrado (Neotropical savanna) - Devecchi, Marcelo F.; Thomas, William W.; Pirani, José R. (Phytotaxa, 2018)
We describe and illustrate two new species of Homalolepis Turcz. (Simaroubaceae), a genus recently reinstated based on molecular evidence indicating that Simaba Aubl. as currently circumscribed is not monophyletic. Both species are dwarf, geoxylic subshrubs with restricted distribution in the Brazilian savanna (cerrado). Homalolepis planaltina is so far known from a single population, in highland fields of southeastern Minas Gerais state, and belongs to H. sect. Grandiflorae. The few known populations of H. pumila are restricted to the Emas National Park in the state of Goiás and belong to H. sect. Homalolepis. We present live pictures of plants of both species in their habitats, as well as drawings of diagnostic features, an identification key to the geoxylic species, detailed descriptions, distribution maps, data on geography and ecology, the conservation status, and comments on morphology and closely related taxa. These two new taxa increase the total diversity of the genus to 28 accepted species.